A Review on Renewable Energy Supply - Goutam Das, Sourav Kumar Das, Palash Pal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The rapid increase in energy consumption, particularly in recent decades, has sparked concerns that the world's petroleum and other resource supplies would be depleted in the near future. The massive usage of fossil fuels has resulted in observable environmental devastation in a variety of ways. Fossil fuels account for almost 90% of total energy usage. The economy and technologies today are heavily reliant on natural resources, which are not replaced, as a result of industrialization and population expansion. Further, on the view of energy efficient system the renewable energy is highly appreciated in future time